Characterization and co-expression analysis of WRKY orthologs involved in responses to multiple abiotic stresses in Pak-choi (Brassica campestris ssp. chinensis) - Tang, Jun (BMC Plant Biol, 2013)
BACKGROUND: The WRKY transcription factor is an important member of the stress-related transcription factors, which mediate diverse abiotic stresses in many plants. However, up until now, the number of WRKY members, and the regulatory mechanisms involved in abiotic stress responses in Pak-choi (Brassica campestris ssp. chinensis), remained unknown. RESULTS: We isolated and identified 56 full-length WRKY cDNAs from a Pak-choi stress-induced cDNA library. The 56 putative BcWRKY proteins were divided into three groups based on structural and phylogenetic analyses. A subcellular localization prediction indicated that the putative BcWRKY proteins were enriched in the nuclear region. Experiments involving BcWRKY25 and BcWRKY40 confirmed the prediction. A total of 22 BcWRKYs were differentially expressed in response to at least one stress condition (abscisic acid, cold, salinity, heat, or osmosis) tested on Pak-choi leaves, and a co-expression analysis indicated stress-inducible BcWRKYs co-regulated multiple abiotic stresses. BcWRKY33, BcWRKY40, BcWRKY53, and BcWRKY70 acted as key regulators and played dominant roles within co-regulatory networks of stress-inducible BcWRKYs. CONCLUSIONS: We first isolated and characterized the 56 stress-inducible WRKY transcription factor family members. A total of 22 stress-inducible BcWRKYs found in leaves can co-regulate multiple environmental stresses by integrating the potential mutual interactions of WRKYs in Pak-choi. This information will be valuable when exploring the molecular mechanisms of WRKYs in response to abiotic stresses in plants.